Faktor-Faktor yang Mempengaruhi Kinerja Penyuluh Pertanian di Provinsi Riau - Irwandi, Putra; Zahra, Zhena Nofhatiaz; Azra, Habibah Nurfaizah; Adetya, Aulia (Fakultas Pertanian Universitas Jember, 2024)
The performance of agricultural extension workers plays a vital role in developing the agricultural sector and improving farmer welfare. This research aims to identify factors that influence the performance of agricultural instructors. The research method used a census of 89 agricultural instructors as respondents. The variables studied include age, education level, work experience, distance to the target location, number of target villages, as well as other factors that have the potential to influence the performance of instructors. Data analysis was carried out using inferential statistical methods to test the relationship between variables. The research results show that of the various factors studied, five variables have a significant influence on the performance of agricultural instructors: age, education level, work experience, distance to the target location, and number of target villages. Age and work experience show a positive relationship with performance, indicating that more senior extension workers tend to perform better. Education level is also positively correlated, indicating the importance of formal knowledge in increasing the effectiveness of extension. The distance traveled to the target location has a negative relationship with performance, indicating that the longer the distance to be traveled, the lower the instructor's performance. The number of villages assisted also influences performance, where there is an optimal point for the number of villages that can be developed effectively. These findings provide important insights for the development of policies and programs to improve the performance of agricultural extension workers